1984
DOI: 10.1007/bf02088636
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance in adolescents: Sleep quality, sleep habits, beliefs about sleep, and daytime functioning

Abstract: This study examined the prevalence and correlates of sleep disturbance in adolescents. Two hundred seventy-seven 9th- and 10th-grade students completed a questionnaire on sleep quality, sleep habits, beliefs about sleep, and daytime mood and functioning. Based on their responses, subjects were classified as good sleepers (66%), occasional poor sleepers (23%), and chronic poor sleepers (11%). Occasional and chronic poor sleepers reported being significantly more depressed, without energy, tense, moody, and irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
38
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 8 publications
6
38
0
1
Order By: Relevance
“…Among these studies, the prevalence of current sleep problems ranged from 6% to 39%. [10][11][12][13][14][15][16][17][18][19][20] The estimate of DSM-IV insomnia in the past 30 days in this study falls at the lower end of this range (9.4%). The 1 other epidemiologic study of adolescents to assess insomnia by diagnostic criteria found a much lower prevalence of DSM-IV insomnia (with or without comorbid disorders) in the past 30 days (4%) than was found here.…”
Section: Prevalence Of Insomniamentioning
confidence: 58%
See 4 more Smart Citations
“…Among these studies, the prevalence of current sleep problems ranged from 6% to 39%. [10][11][12][13][14][15][16][17][18][19][20] The estimate of DSM-IV insomnia in the past 30 days in this study falls at the lower end of this range (9.4%). The 1 other epidemiologic study of adolescents to assess insomnia by diagnostic criteria found a much lower prevalence of DSM-IV insomnia (with or without comorbid disorders) in the past 30 days (4%) than was found here.…”
Section: Prevalence Of Insomniamentioning
confidence: 58%
“…20 Finally, a number of studies have found trouble sleeping to be associated with psychiatric disorders and substance use. [9][10][11][12][13][14][15] Although available data on the degree to which treatment for insomnia may reduce the risk for daytime consequences are limited in both adolescents and adults, there is some evidence that ADHDlike symptoms improve subsequent to treatment for sleep problems. 45,46 Thus, treatment and prevention of insomnia may be important priorities in adolescent health.…”
Section: Significance Of Insomnia In Adolescencementioning
confidence: 99%
See 3 more Smart Citations